Modeling the impact of climate change on streamflow and major hydrological components of an Iranian Wadi system - Nariman Mahmoodi (IWA Publishing, 2021)
Climate change has pronounced impacts on water resources, especially in arid regions. This study aims at assessing the impacts of climate change on streamflow of the Wadi Halilrood Basin which feeds the Jazmorian wetland in southeastern Iran. To simulate streamflow and hydrological components in the future periods (2030–2059 and 2070–2099), projections for the emission scenarios RCP4.5 and RCP8.5 from 11 global-regional climate models and two bias correction methods are used as input data for a hydrologic model that represents the daily streamflow with good accuracy (NSE: 0.76, PBIAS: 4.7, KGE: 0.87). The results indicate a slight increase of streamflow in January and March, due to the higher intensity of precipitation. However, according to the predicted flow duration curves, a decrease for high and very high flow and no remarkable changes for middle, low and very low flow is found under both emission scenarios for both future periods. Compared to the simulated hydrological components for the baseline, a slight increase of evapotranspiration of around 6 mm (4%) and 2 mm (<2%) for the mid- and end of the century is estimated, respectively. Moreover, a substantial drop of water yield of around 36 mm (63%) at mid-century and 39 mm (69%) at the end of the century are projected. HIGHLIGHTS Assess the impacts of climate change on streamflow of a Wadi system.; Evaluate the variation of major hydrological components to gain insights into the variation of streamflow.; Apply a set of different bias correction methods and climate models under two emission scenarios to deal with the potential uncertainties.; Provide valuable information on possible future changes in streamflow and major hydrological components.;